Do we need a simplified model to predict outcomes in patients hospitalized with Acute Decompensated Heart Failure? Results from The Role of Sodium in Heart Failure Outcomes Prediction (‘SHOUT-PREDICTION’) study - Shishir Soni; Yashwant Panwar; Anil Bharani (Indian Heart Journal, 2021)
Context: Hyponatremia is associated with high in-hospital mortality in patients with acute decompensated Heart Failure (ADHF) and is one of the components in various risk scores in heart failure (HF). However, some risk scores predict outcomes in these patients without using hyponatremia as its component. Aim: The study was aimed to evaluate the relationship between serum sodium levels at admission and clinical outcomes during the in-hospital course and three months’ follow-up, in patients admitted in the intensive cardiac care unit (ICCU) with ADHF. Methods and material: This was a single-center prospective, observational study in which 130 consecutive patients admitted with ADHF were observed for clinical characteristics and blood investigation at admission and their clinical outcomes during the in-hospital course and follow-up of 3 months. Results: Hyponatremia and systolic blood pressure (SBP) both were found to be the independent predictor of in-hospital mortality. The SXS score (calculated as a product of SBP and serum sodium, divided by 1000) as a new prediction variable was significantly associated with in-hospital mortality and was compared with the Get with the guideline HF (GWTG-HF) score and ADHF national registry (ADHERE) score. The SXS score showed the best overall accuracy in predicting in-hospital mortality [area under the curve (AUC) = 0.899] as compared to the ADHERE (AUC = 0.780) and the GWTG (AUC = 0.815). Conclusions: A score derived from the product of serum sodium and SBP (SXS score) had a significant association with in-hospital mortality, and better predictive value as compared to GWTG and ADHERE risk score in these patients.